Inertial one-leg squat training and drop jump biomechanics in athletes with anterior cruciate ligament reconstruction after return to sport - Henderson, F. J.; Shimokochi, Y. (The Journal of Strength and Conditioning Research, 2025)
Athletes with anterior cruciate ligament reconstruction (ACLR) display altered jumping mechanics persisting long after returning to sport (RTS). We investigated the effects of flywheel rear leg elevated (Bulgarian) split squat (RLESS) training on single-leg drop jump (SLDJ) biomechanics in athletes with ACLR after RTS. Eleven competitive athletes with unilateral ACLR (546 ± 270 days postsurgery) performed 16 sessions of 1 set of deep knee flexion RLESS until failure in the reconstructed leg (REC) using a flywheel. Using motion capture and force plates, jump height and leg joint contribution were calculated during a 30-cm SLDJ, alongside peak vertical ground reaction force (vGRF), lower extremity joint peak angle, displacement, work, peak internal moment, and peak power. After training, the jump height increased in REC (p < 0.05) but not the intact leg (INT), although the jump height in REC remained lower than that in INT. Reconstructed leg knee contribution increased, whereas REC hip contribution decreased, so no bilateral difference remained after training. Although jump height remained unchanged in INT, several kinematic and kinetic variables changed significantly. Vertical ground reaction force showed no significant difference while asymmetry in internal knee varus moment disappeared, suggesting that some risk factors of ACL injury were reduced. Therefore, athletes with ACLR show persistent deficits in jumping performance, but adding 8 weeks of flywheel RLESS in REC can safely improve performance and restore normal joint contribution. Besides, coaches should be aware of possible changes in jumping mechanics in INT despite unchanged jumping performance when monitoring athletes with ACLR.